2011
DOI: 10.1016/j.bbmt.2010.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Cost and Clinical Analysis of Autologous Hematopoietic Stem Cell Mobilization with G-CSF and Plerixafor Compared to G-CSF and Cyclophosphamide

Abstract: Plerixafor plus granulocyte-colony stimulating factor (G-CSF) has been shown to mobilize more CD34(+) cells than G-CSF alone for autologous hematopoietic stem cell transplantation (HSCT). However, many centers use chemotherapy followed by G-CSF to mobilize CD34(+) cells prior to HSCT. We performed a retrospective study of patients who participated in the expanded access program (EAP) of plerixafor and G-CSF for initial mobilization of CD34(+) cells, and compared outcomes to matched historic controls mobilized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
106
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(110 citation statements)
references
References 17 publications
3
106
1
Order By: Relevance
“…A previous retrospective study, comparing plerixafor plus G-CSF (P þ G) with cyclophosphamide plus G-CSF (CM þ G), found that the cost of HSC mobilization and collection increased dramatically when multiple days of G-CSF/plerixafor and apheresis were required. 11 Although the total median mobilization costs were similar in the two groups, P þ G patients had more predictable apheresis schedules, used less resources and had fewer hospitalizations.…”
Section: Discussionmentioning
confidence: 99%
“…A previous retrospective study, comparing plerixafor plus G-CSF (P þ G) with cyclophosphamide plus G-CSF (CM þ G), found that the cost of HSC mobilization and collection increased dramatically when multiple days of G-CSF/plerixafor and apheresis were required. 11 Although the total median mobilization costs were similar in the two groups, P þ G patients had more predictable apheresis schedules, used less resources and had fewer hospitalizations.…”
Section: Discussionmentioning
confidence: 99%
“…G-CSF þ plerixafor has been calculated to be similar in cost to chemo-mobilization. 13 However, chemo-mobilization exposes the patient to the risks of neutropenic fever, hospital re-admission and unpredictable collections. It also can result in weekend collections that increases costs related to staffing.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, chemotherapy mobilization is associated with significant morbidities, including increased risk of infection and rate of hospitalization and excessive cost. [15][16][17]24,35 Retrospective studies have been performed evaluating the role of CY plus filgrastim mobilization after lenalidomide-containing treatment regimens. Collectively, the data reveal that mobilization with CY and filgrastim results in an increased number of CD34 þ cells collected and reduced rate of mobilization failure when compared with mobilization with filgrastim alone.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10] This negative effect, noticed particularly with growth factor mobilization, is at least partially overcome with the use of chemotherapy mobilization, [11][12][13] although this strategy carries higher cost and toxicity. [14][15][16][17] The CXCR4-SDF1-binding inhibitor plerixafor dramatically enhances filgrastim-based CD34 þ mobilization in patients with MM, 18 but is expensive, limiting its use in all patients undergoing mobilization. Preliminary experience suggests that the majority of lenalidomide-exposed patients failing filgrastim mobilization will adequately mobilize CD34 þ cells with filgrastim plus plerixafor.…”
Section: Introductionmentioning
confidence: 99%